Reliability and alliance interdependence : the United States and its allies in Asia, 1949-1969 - Henry, Iain D., 1984- (Cornell studies in security affairs., 2022)
"This book proposes and tests a new theory of how legally discrete military alliances are, in fact, interdependent. It does so using archival research on U.S. alliances in Asia from 1949 until 1969"--